Vocal Characteristics in Traditional Singing (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Traditional singing is an essential component of cultural expression across the world, representing the emotional, historical, and social elements of a community. This paper explores the vocal characteristics present in traditional singing styles, focusing on the physiological, cultural, and aesthetic factors that influence vocal performance. The study investigates various elements such as voice quality, vocal technique, resonance, breath control, pitch, and ornamentation that define traditional singing across different cultures. The research synthesizes data from vocal studies, ethnomusicology, and the history of vocal traditions to present a comprehensive overview of the subject. The findings emphasize the importance of vocal characteristics in preserving cultural heritage, transmitting emotions, and fostering community cohesion.